Magyar szervezetek Argentínában 1945 után - Csikós Zsuzsanna (University of Szeged, Magyar Medievisztikai Kutatócsoport Szeged, 1991)
Among Latin-American countries, Argentina, Brazil and Uruguay have the largest ethnically Hungarian population. From the 1920's there was a continuous immigration to Argentina from Hungary and from the regions populated by Hungarians that were lost in the Treaty of Trianon. Economic emigrants were followed by those fleeing for political reasons as early as the 1930's, but especially after 1945. This is very well reflected in the social heterogenity of the Hungarian community there. The several thousand Hungarians, settled mostly in Buenos Aires, established a great number of different organizations during the 1930's and 1940's with the aim of preserving the shared language, culture and traditions. These organizations were founded on the town district basis, but some were established on non-geographical principles. The most influential of the latter kind in the post—1945 community life was the Centro Húngaro (Hungarian House) and the Buenos Airesi Magyar Egyesület (Buenos Aires Hungarian Association). A greater part of the organizations was formed before World War II, but beginning from the late 1940's their leadership came from the newly arrived immigrants, which determined the political affiliation of the organizations. Besides the publishing of newspapers and books, theatrical life, and the foundation of schools, the different associations and organizations also played an important role in the cultural life of the Hungarian community in Argentina through their strong intention of keeping the community together.
Keywords: Bölcsészettudományok; Történettudomány és régészet